DIGITAL LEARNING MEDIA FOR DEAF STUDENTS IN LEARNING ENGLISH - Putra Pratama; Destia Dwi Mulyani (Universitas PGRI Palembang, 2024)
Thus, this research aims to analyze the need for developing digital-based English learning media for deaf children. This qualitative research involved students and teachers at SLB-B Karya Ibu Palembang. A needs analysis was carried out to identify the sustainable situation of deaf children for the development of digital learning media for English lessons. Interview and observation techniques using two types of instruments in the form of interview guides, observation, and field notes were used to collect information about the English language learning needs of deaf students. Research findings identified several needs that underlie the development of digital learning materials for English lessons, namely inadequate English teachers, text-based teaching materials, and less than optimal teaching and learning processes because they are still textbook-based, while deaf students are visual learners. Therefore, the development of digital learning media is very necessary. One of the digital learning media that can be developed is E-books. By using e-books containing media such as pictures, animations, and videos, learning becomes more fun and easier for teachers and deaf students in teaching and learning English.